2013
DOI: 10.1021/jp4039495
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Multiple Photon Dissociation Action Spectroscopy of Deprotonated RNA Mononucleotides: Gas-Phase Conformations and Energetics

Abstract: The IRMPD action spectra of the deprotonated forms of the four common RNA mononucleotides, adenosine-5'-monophosphate (A5'p), guanosine-5'-monophosphate (G5'p), cytidine-5'-monophosphate (C5'p), and uridine-5'-monophosphate (U5'p), are measured to probe their gas-phase structures. The IRMPD action spectra of all four deprotonated RNA mononucleotides exhibit distinct IR signatures in the frequency region investigated, 570-1900 cm(-1), that allows these deprotonated mononucleotides to be easily differentiated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 48 publications
2
54
0
1
Order By: Relevance
“…In addition to the ground-state conformers, several stable low-energy excited conformers that differ slightly in the orientation of the phosphate ester moiety were also accessed in the experiments. Comparison of the conformations found by these authors for DNA nucleotides vs RNA nucleotides would suggest that the intrinsic difference between the DNA and RNA mononucleotides is most likely not due to their relative conformations but due to the change in their chemical properties induced by the different substituents at the C2′ position (57). By the same technique Ligare et al studied deprotonated clusters of nucleotides and found that unlike in multimer double stranded DNA structures, the hydrogen bonds in these isolated nucleotide pairs are predominantly formed between the phosphate groups, as shown in Figure 8.…”
Section: Ionic Nucleobases and Nucleotidesmentioning
confidence: 99%
“…In addition to the ground-state conformers, several stable low-energy excited conformers that differ slightly in the orientation of the phosphate ester moiety were also accessed in the experiments. Comparison of the conformations found by these authors for DNA nucleotides vs RNA nucleotides would suggest that the intrinsic difference between the DNA and RNA mononucleotides is most likely not due to their relative conformations but due to the change in their chemical properties induced by the different substituents at the C2′ position (57). By the same technique Ligare et al studied deprotonated clusters of nucleotides and found that unlike in multimer double stranded DNA structures, the hydrogen bonds in these isolated nucleotide pairs are predominantly formed between the phosphate groups, as shown in Figure 8.…”
Section: Ionic Nucleobases and Nucleotidesmentioning
confidence: 99%
“…Gas phase experimental and theoretical studies on a series of mononucleotides compared the dependence of the conformations of these systems on the nature of their nucleobase. 35,36 It was found that all RNA and DNA mononucleotides adopt the C3 0 endo conformation of the ribose and the anti-conformation of the nucleobase. Exceptions where found for guanosine-5 0monophosphate and 2 0 -deoxyguanosine-5 0 -monophosphate in which the nucleobase adapts the syn-conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Collision-induced dissociation (CID) is performed to evaluate the fragmentation behaviour of the systems, while infrared multiple-photon dissociation (IRMPD) spectroscopy in combination with quantum-chemical calculations is used to map intramolecular hydrogen bond interactions and deprotonation sites. Related systems such as protonated and deprotonated mononucleotides, [35][36][37][38][39] mononucleotide clusters, 40 protonated and metal-complexed nucleobases [41][42][43][44][45][46][47][48] and phosphate-metal complexes 49,50 have recently been successfully characterized using these methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…[10] This work was quicklyf ollowed by the analysiso fm onohydrated nucleobases. [11] Since those initial studies, IRMPD spectroscopy has been utilized to examineamultitude of speciesr elatedt o DNA constituents, including, nucleosides, [12] nucleotides, [13] nucleobase dimers, [14] and metal-bound species. [15] Significantly less work has been done, however,o nt he examinationo ft he one-electrono xidation products of DNA and its constituent parts (i.e.,n ucleobase radicalc ations)i nt he gas phase.…”
Section: Introductionmentioning
confidence: 99%